-6(x+4)=-18-7x

Simple and best practice solution for -6(x+4)=-18-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+4)=-18-7x equation:


Simplifying
-6(x + 4) = -18 + -7x

Reorder the terms:
-6(4 + x) = -18 + -7x
(4 * -6 + x * -6) = -18 + -7x
(-24 + -6x) = -18 + -7x

Solving
-24 + -6x = -18 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-24 + -6x + 7x = -18 + -7x + 7x

Combine like terms: -6x + 7x = 1x
-24 + 1x = -18 + -7x + 7x

Combine like terms: -7x + 7x = 0
-24 + 1x = -18 + 0
-24 + 1x = -18

Add '24' to each side of the equation.
-24 + 24 + 1x = -18 + 24

Combine like terms: -24 + 24 = 0
0 + 1x = -18 + 24
1x = -18 + 24

Combine like terms: -18 + 24 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| 1m-5=.4m+4 | | 26x-3=180 | | -2m=6m-9 | | 18+2m=60 | | 3(4g+6)=2(6y+9) | | 4x+14=3+7x-7 | | 1+4(-4+2x)=-15+8x | | -8n+2=3+7n+10 | | 5x-120=13 | | 20+9h=92 | | -3x^2+11x+35=7-4x^2 | | -3p+8=6-(10p+3) | | 11=2+2v+7 | | -15=6x+3(4-3x) | | (x+y)(5x^2-2xy+6y^2)= | | -5(1-2x)=-55 | | -6w+(-8)w=0 | | 5(5x+2x)=9(x-3) | | 3x+16=4x+9 | | log(x)=.68 | | 2.68+2.04=-1.02d+6.1 | | -6(v+4)+2v+6=6v+6 | | 4x-11=8x+5 | | 3x-4x+3=32 | | 1.5x+1.5=3 | | 3x+16=91 | | 5x-9-3x=3x-6 | | 4.9x^2+1.85x+55.3=0 | | 10x^2+14x=-x^2+3x+5 | | 30+.5x=21+.65x | | x-7=3(x+5) | | 4x+3=-4+2x+11 |

Equations solver categories